PENGEMBANGAN MEDIA PEMBELAJARAN PAJAK BUMI DAN BANGUNAN SEBAGAI UPAYA PENINGKATAN PEMAHAMAN MAHASISWA PERPAJAKAN - Afifah, Nurul; Sari, Sri Nirmala (Jurnal Analisa Akuntansi dan Perpajakan, 2020)
Land and Building Tax is a material tax. The amount of tax owed determined by the state of tax objects. Errors in understanding tax objects will cause errors in determining tax rates, calculating taxes and determining the tax payable. Learning media such as videos from the Ministry of Finance Learning Center have already been used, but students are still experiencing difficulties because the videos only feature writings or explanations based on the Law.This research aims to facilitate students in understanding the object of Land and Building. The research uses experimental methods in the form of one group pre-test post-test. The phases of this research are (1) identification problems, (2) designingmodels, (3)making models, (4) implementation. Te result showed that the average score of students are increase. Average score in pre-test is 64,17 or equal to BC. By using the models as learning media, the average score in post-test si 92,14 or equal to A. The result indicates that the models successfully increase the understanding of taxation students in perceive Land and Building Tax objects.